Pediatric post‐marketing safety systems in North America: assessment of the current status†. (22nd June 2015) - McMahon, Ann W.; Wharton, Gerold T.; Bonnel, Renan; DeCelle, Mary; Swank, Kimberley; Testoni, Daniela; Cope, Judith U.; Smith, Phillip Brian; Wu, Eileen; Murphy, Mary Dianne
Abstract Purpose It is critical to have pediatric post‐marketing safety systems that contain enough clinical and epidemiological detail to draw regulatory, public health, and clinical conclusions. The pediatric safety surveillance workshop (PSSW), coordinated by the Food and Drug Administration (FDA), identified these pediatric systems as of 2010. This manuscript aims to update the information from the PSSW and look critically at the systems currently in use. Methods We reviewed North American pediatric post‐marketing safety systems such as databases, networks, and research consortiums found in peer‐reviewed journals and other online sources. We detail clinical examples from three systems that FDA used to assess pediatric medical product safety. Results Of the 59 systems reviewed for pediatric content, only nine were pediatric‐focused and met the inclusion criteria. Brief descriptions are provided for these nine. The strengths and weaknesses of three systems (two of the nine pediatric‐focused and one including both children and adults) are illustrated with clinical examples. Conclusions Systems reviewed in this manuscript have strengths such as clinical detail, a large enough sample size to capture rare adverse events, and/or a patient denominator internal to the database. Few systems include all of these attributes. Pediatric drug safety would be better informed by utilizing multiple systems to take advantage of their individual characteristics.